2021
DOI: 10.3390/healthcare10010004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Usability of mHealth Applications on Type 2 Diabetes Mellitus Using Various MCDM Methods

Abstract: The recent developments in the IT world have brought several changes in the medical industry. This research work focuses on few mHealth applications that work on the management of type 2 diabetes mellitus (T2DM) by the patients on their own. Looking into the present doctor-to-patient ratio in our country (1:1700 as per a Times of India report in 2021), it is very essential to develop self-management mHealth applications. Thus, there is a need to ensure simple and user-friendly mHealth applications to improve c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
1
14
0
1
Order By: Relevance
“…There are various ways, such as MCDM methodologies [ 38 , 39 ], MARS, ID3, etc., through which we can determine the usability of T2DM mHealth applications. The purpose of this assessment has been to determine the quality, effectiveness, and functionality of T2DM mHealth applications and to recommend the optimal one for use.…”
Section: Discussionmentioning
confidence: 99%
“…There are various ways, such as MCDM methodologies [ 38 , 39 ], MARS, ID3, etc., through which we can determine the usability of T2DM mHealth applications. The purpose of this assessment has been to determine the quality, effectiveness, and functionality of T2DM mHealth applications and to recommend the optimal one for use.…”
Section: Discussionmentioning
confidence: 99%
“…The use of smartphones and mHealth apps is growing rapidly in India (GroupM, 2020); however, few studies have assessed T2DM mHealth app usability in this context, and we found none that have used the MAUQ, the current gold standard for evaluating mHealth app usability. However, one robust study has evaluated the usability of five self-management T2DM mHealth apps using various multi-criteria decision-making approaches (Gupta et al, 2022). The same study examined simplicity and ease of use and ranked apps based on their analysis of usability and customer satisfaction.…”
Section: Usability Of Mhealth Applicationsmentioning
confidence: 99%
“…Attributes examined included learnability, efficiency, memorability, aesthetics, errors, navigation, readability, cognitive load, provision for physically challenged users and user satisfaction. Attributes with the highest scores among the five apps included readability and learnability (Gupta et al, 2022).…”
Section: Usability Of Mhealth Applicationsmentioning
confidence: 99%
“…Mobile health (mHealth) programs, that leverage the widespread use of cellphones, are a crucial resource for bridging information inequities for underserved and marginalized communities in the global south (Tshikomana and Ramukumba 2022; Gupta et al. 2022), especially in areas such as public health and social services where access to authoritative information is unevenly distributed. Many nongovernmental organizations (NGOs) periodically send automated voice messages to improve health outcomes of beneficiaries.…”
Section: Introductionmentioning
confidence: 99%